Dysautonomia Differentially Influences the Effect of Affective Pain Perception on Quality of Life in Parkinson’s Disease Patients - D. Rada; J. Seco; E. Echevarría; B. Tijero; L. C. Abecia; J. C. Gómez-Esteban (Parkinson's Disease)
Background. Our aim was to evaluate the real effect of dysautonomic symptoms on the influence of affective pain perception on quality of life in PD patients. Methods. An observational cross-sectional study was carried out using 105 Parkinson’s disease (PD) patients of the Movement Disorders Unit, Hospital de Cruces (Bilbao, Spain) [men 59 (56.2%), women 46 (43.85%)]. Statistical analysis was made in order to evaluate the possible association of pain with life quality. Results. Quality of life measured by PDQ-39 (Parkinson’s Disease Questionnaire for quality of life) was statistically associated with affective dimension of pain (PRIA, affective pain rating index). However, the influence of this dimension on PDQ-39 was different in the specific case of PD patients that experimented a high score (>12) in SCOPA-AUT (Scale for Outcomes in PD-Autonomic scale). Conclusions. These results confirm the effect of affective perception of pain in life quality of PD patients, indicating the critical role of autonomic symptoms in the modulation of the influence of pain on quality of life and showing the possible utility of dysautonomia as clinical prognostic indicator of quality of life in PD patients affected by pain.